Gender works in various ways - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1999)
Gender Works shows that the field of gender issues is extremely broad. This book is a multi-authored contribution to development debates on integrating gender issues into development organisations. It focuses on the experience of Oxfam UK over the...